Spiritual leadership among youth: fostering sustainable development towards Islamic values - Ibrahim, Asmawi; Md Rami, Ahmad Aizuddin; Mohd Isa, Mohd Fadle; Olaitan, Ahmed Ahmed (Malque Publishing, 2025)
This study explores the role of spiritual leadership in promoting ethical and sustainable development among youth leaders within an Islamic context. Using a qualitative research design, focus group discussions were conducted with 11 youth leaders from various community organizations, representing diverse leadership experiences and societal roles. This study highlights the importance of spiritual leadership in addressing the unique challenges faced by youth leaders, such as navigating ethical dilemmas, balancing personal and communal responsibilities, and fostering resilience in the face of socio-economic and cultural constraints. By emphasizing leadership qualities rooted in Islamic principles, including justice (adl), compassion (rahma), and stewardship (khalifah), the study underscores the necessity of holistic youth development programs that focus on personal growth, ethical integrity, and community responsibility. The integration of spiritual and ethical training into youth leadership development has been shown to be instrumental in nurturing resilience, strengthening moral decision-making, and fostering a sense of shared responsibility within communities. This study contributes to the broader discourse on leadership by providing empirical evidence and a culturally relevant perspective on the integration of Islamic values into youth leadership. Additionally, it highlights the importance of family, mentorship, and structured leadership training in shaping future leaders who are both morally upright and socially conscious. Furthermore, this approach aligns with the Sustainable Development Goals (SDGs), advocating for leadership models that prioritize inclusivity, social justice, and sustainable community development. By offering a faith-driven, values-based leadership framework, this study provides a pathway for cultivating a new generation of ethical and socially responsible leaders who are equipped to address contemporary global challenges while upholding Islamic ethical principles.